Ciri Bilah Bambu dan Buluh Utuh pada Bambu Tali dan Bambu Ampel - Naresworo Nugroho; Effendi Tri Bahtiar; Azhar Anas (Jurnal Ilmu Pertanian Indonesia, 2013)
Bamboo is a natural resource that can be used as a basic commodity to substitute wood. To determine the use of a basic commodity, it is needed to study the basic characteristic of bamboo, in terms of anatomy, physical, and mechanical properties. Some studies of this topic, especially for engineering purpose, have been done, but the most of them used sample experiment in the form of bamboo culm. Therefore, it is necessary to find out whether experiments using bamboo strip are equivalent with the value of bamboo culm. This study used tali and ampel bamboos. The anatomy observation followed the Manual of Anatomy Practical Work and Wood Identification by Pandit (1991) and Nuryatin (2000), tests were based on Nuryatin’s study (2000). Sample tests for mechanical properties were based on ASTM D 143-94 and modification of ISO 22157-1:2004. The results showed that physical properties of internode of tali bamboo were inferior than that of the node, in contrary to ampel bamboo, which was better than that of the node. For all mechanical properties, internodes of tali and ampel bamboos were better than that of the node. The modulus of elasticity of the bamboo culm was lower 110% than that of the bamboo strip and the modulus of rupture of the bamboo culm was lower 230% than that of the bamboo strip. On the other side, τTk// of the bamboo culm was 15% higher than that of the bamboo strip.